IMPROVING THE QUALITY OF LIFE IN PSORIASIS PATIENT THROUGH HEALTH PROMOTION APPROACH AT HAJI ADAM MALIK GENERAL HOSPITAL, MEDAN, INDONESIA - Meher, Cashtry; Roesyanto, Irma D; Rochadi, Kintoko; Ashar, Taufik (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Psoriasis is a chronic inflammatory skin disease, can affect all ages characterized by reddish plaques that are covered by thick scales of silvery white and firmly bounded. Psoriasis is a skin disease that is difficult to cure because psoriasis can interfere with life quality of life behavior even cause the level of stress for the patient. This study aims to evaluate the effect of health promotion of quality of life of psoriasis patients. Methods: This research is an experiment between pre- and post-test that aims to know the effort of improving the quality of life of psoriasis patient through a health promotion approach. Population in this research is patient of psoriasis in the draft of human rights number 60 people. Then, divide the questioner to the respondents who made twice before the health promotion and after health promotion in the experimental group. Result: The study showed significant differences between pre- and post-test values for quality of life, stress level, and behavior toward health promotion. Data analysis with paired t-test at 95% confidence level, quality of life with lecture method (p=0.001), quality of life (p=0.001), and behavior with method of Booklet (p=0.001). Conclusion: It is recommended for health workers more often to provide health promotion because psoriasis is chronic and recidive disease, it is necessary to improve the quality of service in hospitals by providing education in the form of health promotion in patients not to quickly despair and can comply with doctor’s advice.